(untitled) (Sciences & Technology. A, exactes sciences, 2002)
Andalin, a benzoylphenylurea (BPU) derivative, was evaluated on Culex pipiens L. (Diptera: Culicidae). Treatment was made on newly 3rd- and 4th instar larvae for 24 h. The compound exhibited insecticidal activity and mortality occured after earlier inhibition of their development or by their inability to complete their ecdysis. Treatment resulted in a significant larvicidal effect and in a inhibition of adult emergence. Moreover, the compound disturbed growth and development since several morphological types and an increase in the duration of larval stage were observed. Histological study conducted on 4th instar larval integument, showed that Andalin caused a significant reduction in the thickness of cuticles secreted compared to controls. Thus, Andalin prevent molting in C. pipiens by interfering with cuticle deposition confirming the primary mode of action of this BPU insecticide.